2020
DOI: 10.1200/jco.2020.38.15_suppl.5515
|View full text |Cite
|
Sign up to set email alerts
|

Final overall survival (OS) from PROSPER: A phase III, randomized, double-blind, placebo (PBO)-controlled study of enzalutamide (ENZA) in men with nonmetastatic castration-resistant prostate cancer (nmCRPC).

Abstract: 5515 Background: PROSPER previously demonstrated a statistically significant and clinically meaningful improvement in metastasis-free survival (MFS) (hazard ratio [HR] 0.29; 95% CI 0.24-0.35; P < .001) in men with nmCRPC and rapidly rising prostate-specific antigen (PSA) who received ENZA. When first reported, OS was immature with only 165 of 596 (28%) prespecified deaths. Here we report results from the final OS analysis. Methods: Men with nmCRPC, PSA doubling time ≤ 10 mo, and PSA ≥ 2 ng/mL at screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…Clinical trial data for the approved ARIs apalutamide, darolutamide, and enzalutamide showed that falls and fractures occurred in a minority of patients with nmCRPC treated with these drugs; of the three, darolutamide was associated with the lowest incidence of falls and fractures (Table 1) [15,16,51]. However, this is not to say that one agent is associated with less fracture risk than the others, and as noted above updated data from these trials show that all three ARIs discussed are associated with increased overall survival compared with placebo, providing important treatment options for high-risk nmCRPC patients [27][28][29].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical trial data for the approved ARIs apalutamide, darolutamide, and enzalutamide showed that falls and fractures occurred in a minority of patients with nmCRPC treated with these drugs; of the three, darolutamide was associated with the lowest incidence of falls and fractures (Table 1) [15,16,51]. However, this is not to say that one agent is associated with less fracture risk than the others, and as noted above updated data from these trials show that all three ARIs discussed are associated with increased overall survival compared with placebo, providing important treatment options for high-risk nmCRPC patients [27][28][29].…”
Section: Discussionmentioning
confidence: 95%
“…ADT in terms of statistically significant improvement in metastasis-free survival [15][16][17]. Updated data from the ARI trials also showed increase in overall survival compared with placebo (HR for apalutamide 0.78 [95% CI 0.64-0.96; P = 0.0161]) [27]; HR for darolutamide 0.69 [95% CI 0.53-0.88; P < 0.003] [28]; HR for enzalutamide 0.73 [95% CI 0.61-0.89; P = 0.001] [29].…”
Section: Aris In Nmcrpc and Effects On Bone: Insights From Clinical Tmentioning
confidence: 99%
“…Efficacy and safety update for darolutamide, enzalutamide and apalutamide Final survival data of three phase 3 trials (ARAMIS, PROSPER and SPARTAN) evaluating efficacy and patient risk-benefit of second-generation anti-androgens (darolutamide, enzalutamide and apalutamide) versus placebo for the treatment of nonmetastatic castration-resistant prostate cancer (nmCRPC) were presented [17][18][19]. A detailed overview of outcomes of all three randomized clinical trials are described in Table 3.…”
Section: Nonmetastatic Castration-resistant Prostate Cancermentioning
confidence: 99%
“…The secondary endpoint (PSA progression-free survival) has currently not met criteria to reject the null hypothesis (HR = 0.69; p = 0.02). Concerning side effects, the most Genitourinary cancers-best of ASCO 2020 K short review Table 3 Updated outcome and descriptive parameters of the three phase 3 trials evaluating efficacy of enzalutamide [17], darolutamide [18] and apalutamide [19] versus placebo in the treatment of nonmetastatic castration-resistant prostate cancer common from LuPSMA were dry eyes, dry mouth and thrombocytopenia. The most common grade 3 or 4 toxicity was thrombocytopenia (11%) [20].…”
Section: Metastatic Castration-resistant Prostate Cancermentioning
confidence: 99%
“…MFS had not previously been used as the primary outcome of clinical trials. The main reasons for administering these therapies in nmCPRC patients were: (1) delaying the onset of metastasis may increase OS; this has been demonstrated after increasing follow-up, and enzalutamide, apalutamide, and darolutamide have shown improvements in OS [12][13][14]; (2) a good tolerated and acceptable safety profile in terms of adverse events (AEs) and no evident loss of quality of life for patients.…”
Section: Introductionmentioning
confidence: 99%